All you need to know about gastrinoma today | Gastrinoma and Zollinger‐Ellison syndrome: A thorough update. (11th April 2023) - Chatzipanagiotou, Odysseas; Schizas, Dimitrios; Vailas, Michail; Tsoli, Marina; Sakarellos, Panagiotis; Sotiropoulou, Maria; Papalambros, Alexandros; Felekouras, Evangellos
Abstract: Zollinger‐Ellison syndrome (ZES) is a distinct syndrome characterized by hyperchlorhydria‐induced peptic ulcer disease and chronic diarrhea. It is the result of a gastrin‐excess state caused by a duodenal or pancreatic neuroendocrine tumor referred to as gastrinoma. This gastrin‐secreting neuroendocrine tumor is usually sporadic in nature, or part of multiple endocrine neoplasia type 1 syndrome. The high rate of malignancy associated with gastrinomas substantiates the need for early diagnosis. In order to diagnose ZES with laboratory tests, patients under antacid medication are required to stay off proton pump inhibitors for at least one week and H2 receptor antagonists for 48 h. Fasting serum gastrin level measurement serves as an initial and fundamental diagnostic test, boasting a sensitivity of 99%. Gastrinoma patients will present with a gastrin level greater than 100 pg/mL, while a serum gastrin level higher than 1000 pg/mL, in the presence of gastric pH <2, is considered diagnostic. Since more common causes of hypergastrinemia exist in the setting of hypochlorhydria, ruling those out should precede ZES consideration. Such causes include atrophic gastritis, Helicobacter pylori (H. pylori)‐associated pangastritis, renal failure, vagotomy, gastric outlet obstruction and retained antrum syndrome. The secretin stimulation test and the calcium gluconate injection test represent classic adjuvant diagnostic techniques, while alternative approaches are currently being introduced and evaluated. Specifically, the secretin stimulation test aids in differentiating ZES cases from other hypergastrinemic states. Its principle is based on secretin stimulation of gastrinoma cells to secrete gastrin, while inhibiting normal G cells. The rapid intravenous infusion of 4 μg/kg secretin over 1 min is followed by gastrin level evaluation at specific intervals post‐infusion. Localization of the primary tumor and its metastases is the next diagnostic step when gastrinoma‐associated ZES is either suspected or biochemically confirmed. Endoscopic ultrasound has showcased sensitivity as high as 83% for pancreatic gastrinomas and is considered the primary modality in such cases, although its tumor detection rates are substantially lower in duodenal lesions. Gallium‐68 radiotracers, especially DOTATOC with positron emission tomography, are currently setting the standard in tumor localization, enhancing traditional imaging techniques and showcasing high sensitivity and specificity. Although gastrinomas have been reported in various anatomic locations, the vast majority arise in a specific site named the "gastrinoma triangle", involving parts of the duodenum, pancreas and extra‐hepatic biliary system. Proton pump inhibitors serve as the cornerstone of symptomatic ZES treatment. Surgery is routinely performed in localized sporadic ZES, irrespective of imaging results. ZES in multiple endocrine neoplasia type 1 requires work‐up for evaluation and treatment of hyperparathyroidism, while surgery might be an option for selected cases. In cases of advanced and metastatic disease, there is a variety of potential treatments, ranging for somatostatin analogs to chemotherapeutic drugs, liver‐directed therapies and liver transplantation, while neither hepatic metastases, nor locally invasive disease necessarily preclude surgical management. This article thoroughly and critically reviews available literature and provides an extensive and multidimensional overview of ZES, along with current controversies regarding management of this disease. Abstract : This review presents an overview of the diagnosis and treatment of Zollinger Ellison syndrome, while dealing with existing controversies with regard to its management nowadays.